Time-Frequency Feature Extraction Method for Weak Acoustic Signals from Drill Pipe of Seafloor Drill - Jingwei Xu; Buyan Wan; Weicai Quan; Yi Xi; Xianglin Tian (Journal of Marine Science and Engineering)
The acoustic signals of the drill pipe of a seafloor drill present weak features under noise interference such as marine environmental noise and the mechanical vibration of the seafloor drill. Accurately extracting the features of the weak acoustic signals of a drill pipe under a strong background noise is an effective means of realizing wireless acoustic communication for a seafloor drill. However, the existing short-time Fourier transform and wavelet transform methods have the defects of fixed window length, wavelet basis function, and decomposition layers, which lead to the inability to accurately extract the weak acoustic signal features of a drill pipe. To overcome these challenges, this study investigates the application of S-transform (ST) in the weak acoustic signal feature extraction of a seafloor drill pipe based on its fundamental principles. Firstly, a time-frequency analysis of the drill pipe’s acoustic signal using ST is conducted, which yields the distribution of the signal across the time and frequency axes. Secondly, singular value decomposition (SVD) is applied to mitigate the noise within the time-frequency matrix. Finally, the noise-reduced time-frequency matrix is analyzed to extract the subtle features of the acoustic wave present within the signal. In order to more accurately assess the differences between the different time-frequency analysis methods in the extraction of weak acoustic wave signals, short-time Fourier transform, wavelet transform, and ST are used to extract the weak acoustic wave characteristics of the drill pipe, respectively. The results show that the ST-based method can effectively improve the accuracy of weak acoustic wave signal feature extraction and provide strong support for reliable transmission of cone penetration test data from the seafloor drill.